The Role of Degree of Relevance in Assessing Translation of Satire - Rahmat Wisudawanto; Myrna Laksman Huntley (Universitas Nahdlatul Wathan Mataram, 2022)
Translation quality assessment is based on the translator’s fulfillment in transferring the message. In the case of translating satire, it must consider adequacy aspects. This paper aims to analyze the translation of satirical utterances using the perspective of relevance theory. Based on this theory, the translation satire and its source expression should result in similar interpretations. The translators are not only required to translate the messages of the satire from the source text (ST) into the target text (TT), but they must also produce interpretative resemblance of the same relevance degree. This research uses qualitative method and aims to analyze the degree of relevance in the translation of satire. The data used satire in Animal Farm and its translation in the Binatangisme novel. The satirical utterance in the ST will be analyzed employing the satire classification. The findings indicate that degree of relevance determines the interpretative resemblance, the similarity of implicated conclusion, and success of communication. The degree of relevance contributes to the translation of satire.